Red Hook summer [videorecording (DVD)] - Lee, Spike; Byrd, Thomas Jefferson, 1960-; Brown, Jules; Lysaith, Toni; Parker, Nate, 1979-; Peters, Clarke (Spike Lee's Chronicles of Brooklyn series, 2012)
The latest in Spike Lee's Chronicles of Brooklyn series, RED HOOK SUMMER tells the story of Flik Royale, a young boy from Atlanta who has come to spend the summer with his religious grandfather, Bishop Enoch Rouse, in the housing projects of Red Hook. Between his grandfather's preaching and the culture shock of city life, Flik's summer appears to be a total disaster, until he meets Chazz Morningstar, a girl his age, who shows Flik the brighter side of Brooklyn.